The Influence of the Implementation of E-Filling and E-Billing on Individual Taxpayer Compliance with Tax Socialization and Understanding of the Internet as Moderating Variables - Pradilatri Kemuning; Yustiana Djaelani; Dwi Yana Amalia Sari Fala (Economics, Business, Accounting & Society Review, 2022)
The purpose of this study was to analyze the effect of implementing the E-Filling and E-Billing System on the Compliance of Individual Taxpayers with Tax Socialization and Internet Understanding as Moderating Variables. Sampling technique using Convenience Sampling. The population in this study are individual taxpayers who have used E-Filling and E-Billing, the total sample is 100 respondents. The hypothesis testing used is the validity test, reliability test and classical assumption test. The hypothesis test used is multiple linear regression and Moderated Regression Analysis. The results showed that the implementation of the e-filling and e-billing system had a positive effect on individual taxpayer compliance, tax socialization strengthened the relationship between the e-filling system implementation and individual taxpayer compliance, tax socialization could not moderate the implementation of the e-billing system on compliance. individual taxpayers and internet understanding cannot moderate the application of e-filling and e-billing systems to individual taxpayer compliance.